Engaging with fragile and conflict-affected states: An alternative approach to theory, measurement and practice - Michael Woolcock (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The coherence and effectiveness of engagement with the world's 'fragile and conflictaffected states' - beyond ethical imperatives and geo-strategic considerations - turns on answers to two vexing questions. First, on what defensible basis is any given country, at any given historical moment, deemed to be (or not to be) 'fragile'? Second, if a defining characteristic of state fragility is low levels of capability to implement core responsibilities, how can international agencies best support domestic public organizations to acquire capability? The first issue may appear to be a methodological one (wherein more and better data would provide a firmer empirical foundation on which to base key decisions) but any determination, especially of marginal cases, must also be grounded in a correspondingly comprehensive theory of change. Similarly, the optimal response to the second issue may appear to be importing technical and rigorously verified ('best practice') solutions, but in fact it is more likely to require a qualitatively different strategy, one able to experiment with alternative design specifications and adapt in real time to changing contextual realities (thereby iterating towards customized 'best fit' solutions). To this end, an alternative approach to the theory, measurement and practice of engaging with fragile states is outlined, in the spirit of rising concerns across the development community that prevailing strategies have demonstrably reached the limits of their effectiveness.
Keywords: D73; O17; O19; 330; conflict; fragile states; institutional change; measurement; security